PENGEMBANGANMODULFISIKA TOPIK GEJALAGELOMBANG DISEKOLAH MENENGAH ATAS (SMA) NEGERI3JAYAPURA - RUSTAMAJI RUSTAMAJI; TRIWIYONO TRIWIYONO (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2018)
This research aimed at creating module physics with the topic waves phenomenathatwasrelevanttobeusedatschoolthatcarryoutasystemofsks.Themethod usedwasresearchanddevelopmentwithphases:preliminary study (define),programdesigning (design) anddevelopment(develop).The module designwasbasedonthe resultof the preliminary study.Thentheprogramwasjudgedby expertsandpilottestedonthirty studentsof XI classofSeniorHighschool3Jayapura,usingonegrouppretest-posttestdesign.Thenwider scale tryoutusinga non-equivalentgrouppretest-posttestquasiexperimentaldesign,andwas conducted on sixtyone students at the same school. Conclusions of the research were 1) characteristics ofthe modulephysics with the topicwaves phenomena, amongothers,self instructional,selfcontained,standalone,adaptive,anduserfriendly. 2)theapplication ofphysics modulewavesphenomenainthelearningtopicscansignificantlyimprovestudents'masteryofconcepts,3)prominenceofwavesphenomena,amongothers,haveacompletemodulestructure,equipped withthelearnerworksheets,completewithmathematicalequations,andsmartsolution.4)alimitation of thismoduleis not equipped with an exercise problems. Keywords: Research, physics module, students, phenomena.